The Street: Enhancing self-confidence and activities of daily living assessment experience in nursing students through drama-based learning (Journal of Applied Learning and Teaching, 2024)
This study investigated the impact of a drama-based patient pathway, ‘The Street’, on pre-registration nursing students’ perceived self-confidence and experience in assessing activities of daily living (ADL). Utilising an interpretative constructivist approach and narrative inquiry, the study involved 80 students specialising in various nursing fields, with focus groups held after the sessions. Key themes emerged, including authenticity, the story, practice learning, and practice application. The findings suggest that ‘The Street’ can enhance students’ self-confidence and holistic assessment experience, thus contributing to the development of teaching and learning resources in nursing education.